An interesting case of anhidrosis - K., Shraddha Kedlaya; A., Gunasekaran; Veeramalai, Ravikumar; P., Lenin Sankar; Subramanian, Sivakumar; Ramesh, Sindhu Belavadi; Duraisamy , Laksheeba (International Journal of Research in Medical Sciences, 2023)
Ross syndrome is a rare syndrome of autonomic dysfunction which is characterized by segmental hypohidrosis/ anhidrosis, Adie tonic pupil and hyporeflexia/areflexia. Exact etiology is not known. It was first described in 1958 and approximately 50 cases have been described so far globally. We hereby report a case of segmental anhidrosis of left face, left upper limb and left side of chest with 3-year duration in a 26-year-old man who also had Adie’s tonic pupil in right eye and global areflexia on examination.